Analisis Employee Engagement dan Kompetensi terhadap Kinerja Pekerja pada Perusahaan Konstruksi - Yamali, Fakhrul Rozi; Yusiana, Venny; Adisetiawan, R.; Putri, Ririn Noviyanti (Universitas Batanghari Jambi, 2026)
The purpose of this study is to analyze the simultaneous and partial influence of employee engagement and competence on worker performance in construction companies. The population of this study was construction workers in companies affiliated with the Jambi Association of Companies. Data collection was conducted through questionnaires using a cross-sectional study approach with a minimum sample size of 102 construction worker respondents. The results showed that simultaneously and partially there was a positive and significant influence between employee engagement and competence on worker performance in construction companies.